Relationship of Economics with Other Subjects: The Impact of Economics on Various Disciplines (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Economics is the most popular subject in the present time. It’s popularity can be gauged from the fact that it is being taught in all the disciplines. It was already a part of curriculum of Arts and Commerce lately science students are also studying it as a compulsory paper. It has become popular more because of the need than anything else. Economics as it has emerged is a science of choice. It is a choice between scarce means and unlimited resources. This is one problem which every individual faces whether he is a doctor, an engineer, a pilot, an actor or a sportsperson. He has to make a choice which leaves him completely satisfied. So why not study the theory related to science of choice?Economics as a subject has a profound effect on almost all the subjects in the world. There is a common thread which connects these subjects with economics. Economics is a guiding light and throws light on the most difficult problem which a man faces choice. If a person knows how to choose then he will always be on the right and will be a boon for the society. Only when we fail to make right choices in the world that we end up in distress, agony, remorse and all the other negative feelings. Economics which is both positive as well as normative that is it tells not only what is but also what ought to be. It not only presents us with how to choose but also what choices should be done.